Gratitude to God: Brief Prompts Do Not Increase It, Wording of Questions Matters, and Belief in a Loving, Powerful, Gift-Giving God Remains Central - Exline, Julie J. (Religions, 2022)
When good things happen, what thoughts elicit gratitude to God (GTG)? Building on work highlighting divine attributions and appraisals, we examined whether consciously priming people to think about God would increase subsequent reports of GTG. U.S. adult participants (N = 553) completed an online survey asking them to describe a positive event from the past month. They were then randomly assigned to one of six conditions, five of which brought up beliefs about God or the idea that God might work indirectly through natural events. Contrary to preregistered predictions, there were no statistically significant differences between conditions on an open-ended or a Likert measure of GTG. Yet GTG reports differed dramatically between the open-ended question (only 20% of participants reported GTG) and a Likert item (81% of participants, and 93% of those who believed in God, endorsed some GTG). The most endorsed response on the 5-point Likert scale was 5, indicating that most people reported feeling extremely grateful to God. These results suggest that the methods used to assess GTG could have a major impact on conclusions about GTG prevalence. Yet, regardless of assessment method, and directly replicating earlier finding, several factors emerged as consistent GTG predictors: religiousness, belief in a loving, powerful, and generous God with positive intentions, attributing the positive event to God, feeling loved in response, and framing the event as a gift from God.